Komparasi Tarif Odontektomi Untuk Perhitungan Tarif Riil Rumah Sakit, Ina-Cbgs Dan ABC Pada Rsgm Unhas - Sintha Kesuma Dewi (Program Studi Magister Manajemen Rumah Sakit, Jenjang Pasca Sarjana (S2), Pasca Sarjana Universitas Muhammadiyah Yogyakarta, 2021)
Determination of tariffs based on INA-CBGs causes polemics for the Hospital, because in some cases, the rates applied have experienced a difference when compared to the previous tariff. This fare difference, can be a benefit for the hospital but can also increase the burden on the hospital. One of the rates that makes a difference in hospitals is the treatment of impacted teeth. The problem with odontectomy measures is whether the INA-CBGs tariff can cover all costs in the odontectomy treatment service and whether the tariff is effective and efficient in odontectomy measures. This research is triangulation using secondary hospital data in 2019, is a case study that aims to analyze the unit cost or unit cost of Odontectomy based on Clinical Pathway with Activity Based Costing method which aims to compare it with the rates set by the Dental & Mouth Hospital of Hasanuddin University and INA-CBG rates. The cost calculation method uses the ABC (Activity Based Costing) method, allocating direct costs by calculating the costs of activities that occur using a cost driver based on the time of activity. There is a difference between the INA-CBGs odontectomy rates and the normal rates based on their qualifications. Efficiencies between INA-CBGs and normal rates for inspection activities (52.7%), lifting seams (76.3%) and controls (72.9%) for mild, moderate and severe odontectomy. There was an inefficient difference between INA-CBGs and normal rates for registration (100%), panoramic radiology (5.8%) and mild odontectomy (424.2%), moderate odontectomy (597.3%) and severe odontectomy (169.01%) ). The compilation of the unit cost tariff design against the Clinical Practice Guidelines based on the ABC method obtained a mild odontectomy rate of Rp. 1,602,293, -; moderate odontectomy of Rp. 1,773,293 and severe odontectomy of Rp. 1,944,293.